DAMPAK TINGKAT PENGUNGKAPAN INFORMASI PERUSAHAAN TERHADAP VOLUME PERDAGANGAN DAN RETURN SAHAM: PENELITIAN EMPIRIS TERHADAP PERUSAHAAN-PERUSAHAAN YANG TERCATAT DI BURSA EFEK JAKARTA - Junaedi, Dedi (UI Scholars Hub, 2005)
The purpose of this study is to evaluate the effect of disclosure level to market indicators, such as trading volume activity (TVA) and stock returns. This study also tries to evaluate the difference in market indicators for companies with differences in disclosure level: comprehensive and non-comprehensive. This study adopts content analysis approach in generating disclosure index, using data from annual reports of firms listed in the JSX in the periods of 2000 - 2002. This study uses mean comparison analysis and regression analysis, both linear and hgistic, in testing the effect of disclosure level to market indicators of companies with comprehensive and non-comprehensive disclosure. This study does not provide empirical evidence to support the effect ofdisclosure level to both market indicators. However, this study finds that there is a difference in TVA between companies with comprehensive and non-comprehensive disclosure. These results lead to a conclusion that disclosure in the annual reports may still not be a matter of considerable interest and importance to investors. This study also finds that firm size and reported income affect disclosure level.